2015
DOI: 10.5392/jkca.2015.15.02.344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment of Silane Coupling Agent in MPS Concentration on the Shear Bond Strength between Self Curing Resins and Heat Curing Resin

Abstract: The purpose of this study was to evaluate the effect of the surface treatment of widely used in dental of silane coupling agent concentration on the shear bond strength of denture base resin and self curing resins. Denture base resin surface was treated with silane coupling agent concentration, after self curing resins were injected shear bond strength was measured. The results of silane coupling agent(MPS) concentration on the shear bond strength of Vertex self curing resin showed that the value of 5%, 7% gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that when the concentration of silane is too high or too low, the bond strength between the inorganic material and the silane is not strong and the silane layer itself acts as a weak part. 38 Only ESPE Sil was used in this study, and additional research on the bond strength according to the silane concentration in 3D printing resin is required.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when the concentration of silane is too high or too low, the bond strength between the inorganic material and the silane is not strong and the silane layer itself acts as a weak part. 38 Only ESPE Sil was used in this study, and additional research on the bond strength according to the silane concentration in 3D printing resin is required.…”
Section: Discussionmentioning
confidence: 99%